DNA double-strand breaks and micronuclei in human blood lymphocytes after repeated whole body exposures to 7T Magnetic Resonance Imaging - Fatahi, Mahsa; Reddig, Annika; Vijayalaxmi; Friebe, Björn; Hartig, Roland; Prihoda, Thomas J.; Ricke, Jens; Roggenbuck, Dirk; Reinhold, Dirk; Speck, Oliver (NeuroImage (Orlando, Fla.), 2016)
To examine the extent of genetic damage, assessed from deoxyribonucleic acid (DNA) double-strand breaks (DSBs) and micronuclei (MN) in peripheral blood mononuclear cells obtained from individuals repeatedly exposed to 7T Magnetic Resonance Imaging (MRI). The study protocol was approved by the local ethics committee. Informed consent was obtained from 22 healthy, non-smoking, non-alcoholic male individuals, who had never undergone radio-/chemo-therapy, scintigraphy, and had not undergone X-ray examination one year prior blood withdrawal. Eleven participants were repeatedly exposed to 7T and 3T MRI while working with/around scanners or frequently participating as 7T and lower field MRI research subjects (mean age 34±7years). The other half was never exposed to 7T or lower field MRI and served as controls (mean age 33±9years). The damage in lymphocytes was assessed using anti-γH2AX immunofluorescence staining of DNA DSBs and by quantification of MN. Isolated cells were further exposed in vitro to 7T MRI either alone or in the presence of the DNA damaging drug etoposide, to determine if there is any additional combined effect. The kinetics of DNA damage repair were examined. The mean base-level of γH2AX foci/cell and incidence of MN between repeatedly exposed and control group were not significantly different (P=0.618 and P=0.535, respectively). The additional in vitro exposure of cells to 7T MRI had no significant impact on MN frequencies and γH2AX foci at 1, 20 and 72h after exposure. Frequently repeated 7T MRI exposure did not result in a detectable increase in genotoxicity indices and alterations of DNA repair kinetics. •We examined the extent of genetic damage in repeatedly exposed individuals to 7T MRI.•No significant differences in γH2AX foci baseline between Rep and Ctr group was found.•Additional in vitro 7T MRI exposure did not result in genetic damage in Rep and Ctl.